Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/math9030221
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion–Advection Equations on a Comb: Resetting and Random Search

Abstract: This review addresses issues of various drift–diffusion and inhomogeneous advection problems with and without resetting on comblike structures. Both a Brownian diffusion search with drift and an inhomogeneous advection search on the comb structures are analyzed. The analytical results are verified by numerical simulations in terms of coupled Langevin equations for the comb structure. The subordination approach is one of the main technical methods used here, and we demonstrated how it can be effective in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
(111 reference statements)
1
21
0
Order By: Relevance
“…( 31) from Ref. [76] (µ → V , σ 2 → 2D, x 0 = 0), as it should be. Finally, the variance is given by var…”
Section: Moments Of Diffusion With Resettingmentioning
confidence: 87%
See 1 more Smart Citation
“…( 31) from Ref. [76] (µ → V , σ 2 → 2D, x 0 = 0), as it should be. Finally, the variance is given by var…”
Section: Moments Of Diffusion With Resettingmentioning
confidence: 87%
“…is the PDF of the drift-diffusion equation without resetting (r = 0) and the initial position is x 0 = 0 [76]), i.e., P r (x, t = 0) = δ(x). The stationary PDF, P * r (x) = lim t→∞ P r (x, t) then takes the following form…”
Section: Preliminariesmentioning
confidence: 99%
“…We note that the case α = 1 in heterogeneous media does not necessarily imply that the process has a Gaussian probability density function (PDF), instead, for instance, exponential or stretched Gaussian forms may be observed [19,20]. We also note that the MSD may also grow exponentially, for a multiplicative noise such as geometric Brownian motion or heterogeneous diffusion processes [21,22,23,24], or logarithmically in strongly disordered environments [25,26].A by-now classical model for heterogeneous systems, popularised by Mandelbrot, are fractals, such as the Sierpiński gasket [27,28,29]. However, such ideal mathematical fractals are often insufficient to adequately describe real fractals such as networks of rivers, blood vessels, or nerve fibres, for which random fractals such as percolation clusters are more appropriate [27,28,29].…”
mentioning
confidence: 95%
“…SR can be phrased as a renewal [67,68] or a non-renewal [69] process. Moreover, SR dynamics was studied for motion in bounded domains [70,71], as well as in monotonic [23,72,73] and non-monotonic potentials [74,75], and under time-dependent resetting [76]. Efficient escape under resetting was investigated [77], and it was shown that interesting phase transitions occur in the parameter space for the optimal resetting rate [63,70,78,79,80].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this myriad of possible applications, several works have systematically investigated the combination of diffusion with stochastic resetting [21][22][23][24][25][26][27][28][29][30][31][32]. Despite this increasing interest in studying diffusion with stochastic resetting, much less attention has been paid towards considering the effect of heterogeneous media [33].…”
Section: Introductionmentioning
confidence: 99%